Ответ: -2/3; 1/2.
Объяснение:
(x - 4)² - 49x² = 0; Имеем разность квадратов
(x - 4)² - (7x)² = 0;
(x-4-7x)(x-4+7x)=0;
(-6x-4)(8x-4)=0;
Произведение равно нулю, если один из множителей равен нулю
-6x-4=0;
-6x=4;
x1=-4/6 = -2/3.
-----------
8x-4=0;
8x=4;
x2=4/8 = 1/2.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ: -2/3; 1/2.
Объяснение:
(x - 4)² - 49x² = 0; Имеем разность квадратов
(x - 4)² - (7x)² = 0;
(x-4-7x)(x-4+7x)=0;
(-6x-4)(8x-4)=0;
Произведение равно нулю, если один из множителей равен нулю
-6x-4=0;
-6x=4;
x1=-4/6 = -2/3.
-----------
8x-4=0;
8x=4;
x2=4/8 = 1/2.